Impact of La3+ and Y3+ ion substitutions on structural, magnetic and microwave properties of Ni0.3Cu0.3Zn0.4Fe2O4 nanospinel ferrites synthesized via sonochemical route. Issue 53 (26th September 2019) - Almessiere, M. A.; Slimani, Y.; Korkmaz, A. Demir; Baykal, A.; Güngüneş, H.; Sözeri, H.; Shirsath, Sagar E.; Güner, S.; Akhtar, S.; Manikandan, A.
Abstract : The best microwave properties for the NSFs were obtained with an LaY concentration of x = 0.08, RL of −40 dB @ 10.5 GHz and absorption bandwidth of 8.4 GHz @ −10 dB. The NSF products show promise as radar absorbing materials in the X-band. Abstract : In the current study, Ni0.4 Cu0.2 Zn0.4 La x Y x Fe2− x O4 ( x = 0.00 − 0.10) nanospinel ferrites (NSFs) were fabricated via an ultrasonic irradiation route. The creation of single phase of spinel nanoferrites (NSFs) was investigated by X-ray powder diffractometry (XRD) and selected area diffraction pattern (SAED). The cubic morphology of all samples was confirmed by scanning and transmission electron microscopies (SEM and TEM) respectively. The UV-Vis investigations provided the direct optical energy band gap values in a narrow photon energy interval of 1.87–1.92 eV. The 57 Fe Mössbauer spectroscopy analysis explained that the hyperfine magnetic fields of Octahedral (Oh) and Tetrahedral (Td) sites decreased with substitution. The paramagnetic properties of NPs decrease with increase of content of doped ions. Investigations of magnetic properties reveal a superparamagnetic nature at 300 K and soft ferromagnetic trait at 10 K. The M s (saturation magnetization) and M r (remanence) decrease and the H c (coercivity) increases slightly with La 3+ and Y 3+ substitution. The observed magnetic traits are deeply discussed in relation with the morphology, structure, magnetic moments and cation distributions. The microwave characterization of the prepared NSFs showed that, dissipation ( i.e., absorption) of incoming microwave energy occurs at a single frequency, for each sample, lying between 7 and 10.5 GHz. The reflection losses (RL) at these frequencies range from −30 to −40 dB and the mechanism of which is explained in the framework of dipolar relaxation and spin rotation. The best microwave properties were obtained with a LaY concentration of x = 0.08 having an RL of −40 dB @ 10.5 GHz and an absorption bandwidth of 8.4 GHz @ −10 dB. With these high values of RL and absorbing bandwidth, LaY doped NiCuZn NSF products would be promising candidates for radar absorbing materials in the X-band.